Transchegaraviy qo'shilish va sotib olish operatsiyalarida nizolarni arbitraj orqali hal qilish - Otajonova Shaxzoda Ulugbek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Arbitration has become one of the preferred dispute resolution mechanisms for resolving disputes arising from cross-border mergers and acquisitions (M&A) transactions. Its impartiality, efficiency, confidentiality, and widespread enforceability provide parties to the dispute with a reliable and effective alternative to litigation. Notably, its use is possible both pre- and post-closing. Despite the risks and challenges, arbitration remains a key mechanism in resolving such disputes.